A Comparative Analysis of Financial Resilience in State-Owned Enterprises in the Construction Sector: A Case Study of PT Hutama Karya, PT Adhi Karya, and PT. Waskita Karya (2022-2024) - Ramadhan Hibatur Rahman; Desgha Lavia Miranda; Destri Hamidah; Hanasya Putri Hanafi.HS; Novia Ardhana; Karin Angelika Putri; Yossinomita Yossinomita (Jurnal Administrasi Terapan, 2026)
This study aims to compare the financial structures including assets, liabilities, and equity of three major state-owned construction enterprises (SOE) in Indonesia: PT Hutama Karya (Persero), PT Adhi Karya (Persero) Tbk, and PT Waskita Karya (Persero) Tbk, over the 2022-2024 period. The research methodology employs a quantitative descriptive-comparative approach using secondary data in the form of audited consolidated financial statements. The sampling technique used was purposive sampling, while data analysis involved vertical analysis to evaluate the composition of the structure, horizontal analysis to identify year-on-year (YoY) trends, and the calculation of the Debt-to-Equity Ratio (DER). The research findings indicate the dominance of PT Hutama Karya’s assets, which reached Rp196.0 trillion in 2024 with non-current assets accounting for 71.20%, reflecting a long-term investment orientation in the infrastructure sector. Conversely, PT Adhi Karya exhibits significant liquidity vulnerability due to the dominance of short-term liabilities, which reached approximately 79%. PT Waskita Karya experienced substantial equity erosion of 51% in 2024, triggered by accumulated losses of Rp1.23 trillion. In terms of leverage, PT Hutama Karya recorded the lowest Debt-to-Equity Ratio (DER) of 0.42x thanks to support from State Capital Injection (PMN), while PT Adhi Karya and PT Waskita Karya exhibited high financial risk profiles with DERs above the 2.0x threshold. This study concludes that there are significant differences in funding strategies and financial health among the three entities, where government support through the PMN instrument is the key differentiating factor in strengthening the companies’ capital structures. Keywords: Comparative Analysis, State-Owned Construction Enterprises, Debt-to-Equity Ratio (DER), Financial Statements, Financial Structure